A rare case of isolated post-traumatic subscapularis abscess in a paediatric patient - Faris Indra Prahasta, Didi Indra; Mohd Anuar Ramdhan, Ibrahim; Ong Lik, Han (DiscoverSys Inc., 2022)
Introduction: Subscapular abscess is an extremely rare condition. To our knowledge there were nine reports on subscapular abscess in the literature, four of them happened paediatric patients. The signs and symptoms could be very subtle making the diagnosis is difficult and often delayed. Case description: We share a rare case of isolated subscapularis abscess with no glenohumeral involvement of a healthy 9-year-old boy following blunt trauma to the shoulder treated with antibiotics and percutaneous drainage with good outcome. Conclusion: Subscapular abscess should be suspected in a child present with fever and shoulder pain. Magnetic resonance imaging is the best modality for diagnosis as plain radiograph would not give any diagnostic help. Surgical drainage combined with antibiotics are the mainstay of treatment. However, percutaneous drainage is one of treatment options especially in paediatric patient as demonstrated in our report.